Kajian Jalan Inspeksi (Check Road) Guna Meningkatkan Keamanan di Sisi Udara Bandar Udara Adi Soemarmo Boyolali - Lina Rosmayanti; Fanji Chaksono; Agoes Soebagio (Jurnal Flight Attendant, 2025)
The airport perimeter is a critical area in aviation security. This study aims to assess the condition of the perimeter inspection road at Adi Soemarmo International Airport in Boyolali and explore improvement efforts. Using a qualitative descriptive approach through observation, interviews, and document analysis, the findings reveal that the inspection road is not fully connected and does not meet technical standards such as width, surface quality, lighting, and drainage. These issues hinder patrol effectiveness and increase security risks. The study recommends infrastructure improvements, installation of lighting and CCTV, and road connectivity enhancements to improve operational efficiency and airport security.